Investigation of the kinetics of anaerobic metabolism by analysis of the performance of elite sprinters - Ward-Smith, A. J.; Radford, P. F. (Journal of Biomechanics, 2000)
The principal motivation for the present work was the study of the kinetics of anaerobic metabolism. A new mathematical model of the bioenergetics of sprinting, incorporating a three-equation representation of anaerobic metabolism, is developed. Results computed using the model are compared with measured data from the mens' finals of the 100 m event at the 1987 World Championships. The computed results closely predict the overall average performance of the competitors over the course of the entire race. Further calculations show the three-equation model of anaerobic metabolism to be a significant improvement over the previous one-equation model. Representative values of time constants that govern the rate of anaerobic energy release have been determined for elite male athletes. For phosphocreatine utilisation, values for 2=0.20 s-1 and 2=3.0 s-1 are consistent with data previously reported in the literature. New values of 3=0.033 s-1 and 3=0.34 s-1 are proposed as offering an improved representation of the kinetics of oxygen-independent glycolysis. For the first time, tentative values for the time constants of ATP utilisation, 1=0.9 s-1 and 1=20 s-1, are suggested. The maximum powers developed during sprinting by oxygen-independent glycolysis, PCr utilisation and endogenous ATP utilisation were calculated as 34.1, 30.1 and 16.6 W kg-1, respectively, with an overall maximum anaerobic power of 51.6 W kg-1. Sample calculations show the mathematical model can be used in principle to derive data on the kinetics of anaerobic metabolism of individual athletes.